2019
DOI: 10.3389/fevo.2019.00373
|View full text |Cite
|
Sign up to set email alerts
|

Echolocation and Stratum Preference: Key Trait Correlates of Vulnerability of Insectivorous Bats to Tropical Forest Fragmentation

Abstract: Habitat loss and fragmentation rank high amongst the most pressing threats to biodiversity. Understanding how variation in functional traits is associated with species vulnerability in fragmented landscapes is central to the design of effective conservation strategies. Here, we used a whole-ecosystem ecological experiment in the Central Amazon to investigate which functional traits of aerial-hawking insectivorous bats best predict their sensitivity to forest fragmentation. During 2014, bats were surveyed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 104 publications
1
47
1
Order By: Relevance
“…As our study system comprises a relatively modest gradient of forest structure (Rocha et al 2017a), the presence of closely related bat lineages in the edge and matrix of small forest fragments could be attributed to selection towards traits determining competitiveness instead of the niche of species, particularly if the niche differences among bat lineages were not strongly related to their phylogeny (Mayfield and Levine 2010;Gerhold et al 2015). Considering the strong sensitivity of several functional traits towards fragmentation (Farneda et al 2015;Nuñez et al 2019) we argue that phylogenetic clustering in habitat of low quality could lead to trait convergence to reduce competition asymmetry between closely-related species (Scheffer and van Nes 2006) and may further decrease the phylogenetic diversity of the assemblage. Thus, despite the ability of large forest fragments to retain amounts of total evolutionary history similar to the interior of continuous forest, the level of forest degradation at the edges and in the matrix still has a negative effect on the phylogenetic diversity of bats at the BDFFP.…”
Section: Discussionmentioning
confidence: 99%
“…As our study system comprises a relatively modest gradient of forest structure (Rocha et al 2017a), the presence of closely related bat lineages in the edge and matrix of small forest fragments could be attributed to selection towards traits determining competitiveness instead of the niche of species, particularly if the niche differences among bat lineages were not strongly related to their phylogeny (Mayfield and Levine 2010;Gerhold et al 2015). Considering the strong sensitivity of several functional traits towards fragmentation (Farneda et al 2015;Nuñez et al 2019) we argue that phylogenetic clustering in habitat of low quality could lead to trait convergence to reduce competition asymmetry between closely-related species (Scheffer and van Nes 2006) and may further decrease the phylogenetic diversity of the assemblage. Thus, despite the ability of large forest fragments to retain amounts of total evolutionary history similar to the interior of continuous forest, the level of forest degradation at the edges and in the matrix still has a negative effect on the phylogenetic diversity of bats at the BDFFP.…”
Section: Discussionmentioning
confidence: 99%
“…Established in 1979, the BDFFP is considered the world's largest and longest-running experimental study on the impact of forest fragmentation on tropical biota [7]. The 80-650 m that separate the experimental forest fragments from CF have already been shown to induce multiple fragmentation-driven changes to the habitat structure of forest fragments and to the composition and abundance of both phyllostomid [26] and non-phyllostomid bats [29]. Canopy is 30-37 m tall, with emergent trees reaching 55 m. Local climate corresponds to Köppen's Af type, with an average annual temperature of 27 • C (maximum: [35][36][37][38][39] • C, minimum: 19-21 • C), and a well-defined dry season from June to October when precipitation drops below 100 mm/month and a rainy season from November to May when precipitation can exceed 300 mm/month [38].…”
Section: Study Areamentioning
confidence: 99%
“…For example, gleaning animalivorous bats are regarded as more susceptible to fragmentation and disturbance than either frugivores or nectarivores [25,26]. However, despite known effects of fragmentation on the vertical stratification of forest invertebrates (e.g., [27]), we know little about the effects of fragmentation on the vertical stratification of bat assemblages (but see [28,29]) as most bat vertical stratification studies targeted only continuous forest [16,[30][31][32][33][34][35] or forest fragments [36]. Yet, these studies have shown that species richness and abundance differ among strata, and that some species can be classified as either understory or canopy specialists.…”
mentioning
confidence: 99%
See 2 more Smart Citations